34.4k views
24 votes
Solve the equation -6 + 6n = 42 for n. A. -6
B. 2
C. 6
D. 8

2 Answers

9 votes

Answer:

D.
\displaystyle 8

Step-by-step Step-by-step explanation:


\displaystyle -6 + 6n = 42 \hookrightarrow (48)/(6) = (6n)/(6) \\ \\ \boxed{8 = n}

*We add six to both sides, then divide the remaining result by six, to get eight.

I am joyous to assist you at any time.

User Dominik Sajovic
by
5.2k points
6 votes

Hey there!

-6 + 6n = 42

6n - 6 = 42

ADD 6 to BOTH SIDES

6n - 6 + 6 = 42 + 6

CANCEL out: -6 + 6 because it gives you 0

KEEP: 42 + 6 because it help solve for the n-value


NEW EQUATION: 6n = 42 + 6


SIMPLIFY IT!

6n = 48


DIVIDE 6 to BOTH SIDES

6n/6 = 48/6

CANCEL out: 6/6 because it give you 1

KEEP: 48/6 because it help solve for the n-value (it actually give you the n-value)


NEW EQUATION: n = 48/6


SIMPLIFY IT!


n = 8


Therefore, your answer is: Option D. 8


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User JonathanKingston
by
5.0k points